TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI GROSIR DAN ECERAN DI TOKO USAHA DAGANG FIKRA BEUREUNUEN - Zul Azimi (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2025)
This study aims to explain the practice of wholesale and retail sembako (basic necessities) trading at Usaha Dagang Fikra Beureunuen and analyze it based on Islamic law. The method used in this research is descriptive qualitative, with data collection techniques including field observations and direct interviews with business operators. The research was conducted at Usaha Dagang Fikra Beureunuen, Pidie Regency, Aceh, focusing on price differences between wholesale and retail transactions and the implementation of Islamic law principles in these transactions. The results show that trading practices in the store meet the pillars and conditions of sale and purchase in Islam; however, the right of khiyar (option to rescind the sale) has not been fully applied. Additionally, improvements are needed in terms of information transparency and price fairness to prevent losses for consumers and small traders in the surrounding area. Better implementation of Islamic law principles will enhance the blessings and fairness in transactions.